Original paper Fibroblast growth factors promote pancreatic cell proliferation in normal and STZ – treated hamsters - Inchovska, Maya; Ogneva, Vesselina; Martinova, Yordanka (Archives of Medical Science, 2006)
Introduction: In various organs cell proliferation and differentiation are controlled by growth factors. The knowledge concerning the implication of FGF family members in pancreatic development is still incomplete. The aim of the present study was to examine the structure characteristics, functional and proliferative activity of normal and diabetic hamster pancreatic cells following treatment with FGF 1, 2 and 7 in vitro. Material and methods: We have studied three groups of healthy hamsters – 5 hamsters at age pnd 1, 10 hamsters at age pnd 5 and 7 hamsters at age pnd 10. We induced experimental diabetes in female hamsters during the first 24 hours after mating of female and male hamsters by intraperitoneal streptozotocin (STZ) administration at a dose of 65 mg/kg. For the study we used only these animals from the litter that had a blood glucose level over 11 mmol/l. Three groups of diabetic hamsters were investigated – 20 hamsters at age pnd 1, 20 hamsters at age pnd 5 and 20 hamsters at age pnd 10. The following methods were used: H.E. staining, P/A.F. staining and histoautoradiography. Results: Light microscopic studies showed active synthetic processes in pancreatic cells under the influence of investigated FGFs. In our experimental model of diabetes the labelling index of pancreatic cells was higher than in the corresponding groups of healthy hamsters. The most important finding in our study was that FGF2 at a concentration of 10 ng/l has shown the most prominent effect in normal hamsters at age pnd 10 and in the streptozotocin-treated hamsters at age pnd 5. Conclusions: We conclude that FGF 2 stimulates the initial process of cell aggregation and cluster formation. Our study provides evidence for a positive regulatory effect of FGF1, FGF 2 and FGF 7 on the expansion of the pancreatic cell mass in normal and streptozotocin-treated hamsters.